2020
DOI: 10.1103/physrevresearch.2.033302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interorbital scattering on superconductivity in doped Dirac semimetals

Abstract: Unconventional superconductivity has been discovered in a variety of doped quantum materials, including topological insulators and semimetals. A unifying property of these systems is strong orbital hybridization, which leads to pairing of states with nontrivial Bloch wave functions. In contrast to naive expectation, however, many of these superconductors are relatively resilient to disorder. Here we study the interplay of superconductivity and disorder in doped three-dimensional Dirac systems, which serve as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 80 publications
3
16
0
Order By: Relevance
“…As we can infer from Table VI, all gap functions have a finite fitness measure, whose size depends on the details of the microscopic Hamiltonian. This aspect was already emphasized in previous works [24][25][26]. However, we also observe that the evolution of the share of symmetric configurations, S i (n), affects the scattering rate, which is a feature that does not depend on the structure of the Hamiltonian, but on the distribution of impurities.…”
Section: Op Orbitals From Different Atomssupporting
confidence: 77%
See 1 more Smart Citation
“…As we can infer from Table VI, all gap functions have a finite fitness measure, whose size depends on the details of the microscopic Hamiltonian. This aspect was already emphasized in previous works [24][25][26]. However, we also observe that the evolution of the share of symmetric configurations, S i (n), affects the scattering rate, which is a feature that does not depend on the structure of the Hamiltonian, but on the distribution of impurities.…”
Section: Op Orbitals From Different Atomssupporting
confidence: 77%
“…Specific results for Cudoped Bi 2 Se 3 report that the robustness of the superconducting state depends not only on the superconducting order parameter, but on details of the electronic structure in the normal state [24]. Recently, this understanding was corroborated by a more complete analysis of the sensitivity of pairing states to various scattering potentials in two-orbital systems [25,26].…”
Section: Introductionmentioning
confidence: 90%
“…One would, thus, naively expect that any superconducting state with a significantly momentum-dependent order parameter, such as the k-dependent phases of (k) above, should be strongly suppressed [74,75]. However, more recent theoretical works [20][21][22][23][24] have shown that the pair-breaking effect of impurities can be significantly reduced in the presence of spin-orbit coupling; this is also confirmed by experiments [25][26][27] indicating that the critical temperature of pairing states transforming under a nontrivial representation of the point group might only be weakly suppressed in the presence of spin-orbit coupling-even when l becomes smaller than ξ (or even of the order of the Fermi wavelength). The basic reason for this protection mechanism is that matrix elements of an impurity potential between certain pairs (k 1 , k 2 ) of momenta can be suppressed due to spin-orbit mixing and that only certain scattering processes are pair breaking.…”
Section: Relevance Of Disordermentioning
confidence: 99%
“…Nematic superconductivity is suppressed by the large disorder that confirms results of Refs. [27][28][29]. The critical temperature depends on the parameter ζ that determines both the critical temperature in a clean case and robustness against the disorder according to Eqs.…”
Section: Effects Of Scalar Impuritiesmentioning
confidence: 99%
“…In Refs. [26][27][28][29] effects of the disorder on critical temperature of nematic superconductor was studied. It was found that density disorder decreases critical temperature for the nematic order parameter.…”
Section: Introductionmentioning
confidence: 99%